1999
DOI: 10.1161/01.hyp.34.3.398
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence That Endogenous Dopamine Modulates Sympathetic Activity in Man

Abstract: Abstract-Dopamine receptors type 2 (D2)-like receptor blockers cause an increase in the norepinephrine response to intense physical exercise. However, during intense physical exercise, D2-like antagonists also cause an increase in the epinephrine response, which itself might cause an increase in plasma norepinephrine through the activation of ␤2 presynaptic receptors. Therefore, we evaluated the effect of domperidone, a D2-like antagonist, on the norepinephrine response to physical exercise in 6 Addison patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…In previous studies, 26,27 we have demonstrated that D 2 -like receptors are present on human chromaffin cells and that they An example of power spectra at baseline (top), after bromocriptine administration (middle), and after DMϩbromocriptine treatment (bottom), with subjects in the supine position (left) and the sitting position (right). PSD indicates power spectrum density.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, 26,27 we have demonstrated that D 2 -like receptors are present on human chromaffin cells and that they An example of power spectra at baseline (top), after bromocriptine administration (middle), and after DMϩbromocriptine treatment (bottom), with subjects in the supine position (left) and the sitting position (right). PSD indicates power spectrum density.…”
Section: Discussionmentioning
confidence: 99%
“…22 As leptin-binding sites have been found in regions of the brain that are important in cardiovascular control, 23 and chronic leptin infusion exerts longterm effects on cardiovascular and renal function, 12,24 it seems conceivable that leptin could modify cardiovascular function through central nervous system effects. Evidence suggests that endogenous DA modulates NE synthesis and secretion in the noradrenergic neurons 25 and -at least in part -leptin release and OB gene expression in adipose tissue. As DAergic activity is reduced in subjects with hypertension and obesity, 3 this could explain in part that obesity, 26 sympathetic hyperactivity, 27 and hyperleptinemia 28 are associated with hypertension.…”
mentioning
confidence: 99%
“…During intense sympathetic activation, as induced by physical exercise, D 2 -like antagonists cause a larger increase in plasma norepinephrine than placebo (31). These data suggest that during a high degree of sympathetic stimulation, endogenous dopamine, which is co-released with norepinephrine by nerve endings, is sufficiently increased in the synaptic cleft to modulate and inhibit norepinephrine release (29).…”
Section: Possible Mechanisms In the Inhibition To Dopamine And Quinpimentioning
confidence: 88%
“…This could explain the bradycardia induced by the highest doses of dopamine and quinpirole (see Table 2). The source of endogenous dopamine acting on the presynaptic D 2 -receptors is still unknown (29). Other studies on heart rate have shown that D 2 -like antagonists did not modify plasma norepinephrine in humans when administered in conditions of rest or mild sympathetic stimulation, which is achieved by standing, a cold pressor test, or hand-grip (30).…”
Section: Possible Mechanisms In the Inhibition To Dopamine And Quinpimentioning
confidence: 99%